STUDENTS’ ONLINE LEARNING READINESS AMID THE COVID 19 OUTBREAK: MCO PHASE 1 - Sabariah Abd Rahim; Wan Hurani Osman; Mohammad Aqmal Hafidz Musa; Nor Dawirah Rahman, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Teaching on digital platforms has now become the trend, and whether it is language apps, virtual tutoring, or video conferencing tools, there has been a significant rise in usage since the Covid-19 outbreak. In this regard, the study investigated students’ readiness towards online learning during the Malaysia Movement Control Order (MCO) Phase 1. 120 students were asked to respond to a questionnaire. However, only 98 students had responded to the questionnaire. In general, the finding shows that the students were not fully ready for online learning mainly due to the limited access to the internet, and because of this limitation, they prefer to have downloadable videos and lecture presentation slides that they can access at any time asynchronously. This study has implications on identifying students’ learning needs for the digital language classroom as the base for designing the learning materials.